Portrait of the Existence of Religious Organization in Serving the Ummah in Central Java Province: Tracing the Existence of Mathla'ul Anwar - Nuriyanto, Lilam Kadarin; Rachmadhani, Arnis; Rosidin, Rosidin; Fauzah, Titi Isnaini; Samidi, Samidi (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
As social creatures, humans naturally cannot live without the help of others. Based on those dynamically social interactions, religious organizations –a form of a social group based on equality in both activities and professions– are formed. At the end of the 19th century, the birth of several Islamic organizations was the answer to the Dutch colonialism situation, including the Mathla'ul Anwar. The existence of Mathla'ul Anwar in Central Java Province is still not well known generally, even though it has been established since 1916. This paper would like to raise an issue qualitatively related to tracing the existence and its service to the community in Central Java. Regional management informed some areas that could be traced for the presence of the organization: Salatiga City, Brebes, Banjarnegara, Purbalingga, and Temanggung Regency. The results obtained in this study are, historically, Mathla'ul Anwar was a reorganization of existing management and new management. The community services are mostly in education, where several established foundations were then joining the organization, becoming the power of movement (da'wa) as much support from professionals. The obstacles that existed in running the organization are the limited funding sources and the lack of sustainability and equal guidance for the administrators.